HIV testing and knowledge on mother-to-child transmission among pregnant women attending antenatal care at Vanga Hospital, Democratic Republic of Congo - Junior Mudji; Victoria Olarewaju; Blaise Madinga; Justice Malala; Auguy Kayeye; Yves Horsmans (AOSIS, 2023)
Background. Human immunodeficiency virus (HIV) causes an infectious disease that can be transmitted from an infected mother to her child. Prevention of Mother-to-Child Transmission (PMTCT) programs provide a range of services to women and children that can reduce the risk of vertical transmission of HIV. Unfortunately, PMTCT programs face many challenges in the rural Democratic Republic of Congo (DRC). Methods. A cross-sectional study was conducted among 460 pregnant women attending antenatal care at Vanga Hospital in the Vanga health zone, DRC from March 11th to June 25th, 2019. Serological tests were performed and a pre-tested questionnaire regarding HIV knowledge was given to all participants. Data were analyzed with STATA 13.0. Descriptive statistics of key variables were computed and logistic regression was used to assess the association between participant's characteristics and knowledge of MTCT. Results. Among the participants, 95.4% (439/460) reported that they have heard about HIV, 82.4% (378/460) indicated sexual intercourse as one of the routes of HIV transmission but only 30.4% (139/460) mentioned MTCT as one of the routes. In addition, only 10.1% (46/460) had knowledge of the existence of PMTCT. Participants' age (29 years), education level, previous antenatal care, and previous HIV tests were significantly associated with knowledge of MTCT. Also, age (29 years) and education level were significantly associated with previous HIV test uptake. Most pregnant women 82.3% (376/460) reported that they have never been tested in the past for HIV infection and the prevalence was at 0.9% (4/460). Conclusions. Knowledge of MTCT of HIV, previous uptake of HIV testing, and prevalence was low. The rural setting of Vanga and insufficient HIV sensitization activities are considered contributors to this. While the low prevalence is a positive finding, much needs to be done to improve the uptake of HIV testing and knowledge of HIV MTCT.